Treatment of vasculitic peripheral neuropathy: a retrospective analysis of outcome. - Mathew, L; Talbot, K; Love, S; Puvanarajah, S; Donaghy, M (2007)
BACKGROUND: Vasculitis of the peripheral nervous system (PNS) is rare. There are no controlled treatment trials, and clinical practice is guided by experience from case series and indirectly by analogy with systemic vasculitis. METHODS: We identified patients (n=212) with possible vasculitic peripheral neuropathy (VPN) from the neuropathology and neurophysiology records of two centres over 28 years. Case-notes were available for 181, from which, 106 cases of clinicopathological VPN were identified. Adequate treatment data were available in 100; follow-up data, in 93. RESULTS: Of 106 cases, 95 had systemic vasculitis and 11 had vasculitis confined to the PNS. Pharmacological treatment (94/100 cases) was corticosteroid-based, and included cyclophosphamide in 54; 17 received additional agents. Initial stabilization was achieved in all but six. One-year survival was 90.3%. Of the nine who died in the first years (mean age 73 years), seven had received cyclophosphamide, and all but two had severe, multisystem vasculitis. The neurological relapse rate was 10%. Only one relapse occurred after cyclophosphamide treatment. Outcome was reported as good in 72% (78% in those who relapsed). DISCUSSION: Death and relapse were infrequent in treated patients. Relapse occurred almost exclusively in patients treated with prednisolone alone. Aggressive early treatment with cyclophosphamide may prevent relapse. The current management approach to VPN appears largely effective, especially if cyclophosphamide is used.